International Migration in Nepal: Rates, Drivers and Impacts - Khatiwada, Padma Prasad (Journal of APF Command and Staff College, 2023)
Migration is the process of change in usual place of residence which is taking place both as internal and international having diverse short-term and long-term outcomes. This paper explores these outcomes by analyzing mainly the international migration rates and drivers in Nepal. Using the secondary sources of data, this paper first gives an account on how migration rate is calculated which is a rigorous process and for which authentic data are needed by utilizing the verified sources of data. The paper then highlights the social, demographic, economic, environmental and political drivers of migration. Some drivers primarily influence migration decision-making in the areas of origin while others influence them to pursue for betterment of life. Some more push and pull factors, mainly the disasters and conflicts as 'push' and growing student migration as 'pull' have also drawn a larger and growing attention of policy makers. Nepal being one of the labour sending countries to Malaysia and gulf countries makes its almost one-third of the economy through remittance. Problems related to livelihood and quest for life have been the usual phenomena which are analyzed in this article as drivers. The paper concludes that there is no association between the types of migration drivers and their impacts. Whatever the drivers are, Nepali people migrate to access improved economic and employment opportunities.